Coordination chemistry and metal-involving reactions of amidoximes: Relevance to the chemistry of oximes and oxime ligands - Bolotin, Dmitrii S.; Bokach, Nadezhda A.; Kukushkin, Vadim Yu (Coordination chemistry reviews, 2016)
•Synthesis, properties, and identification of metal-free amidoximes.•Synthesis and structural features of amidoxime complexes.•Comparison of chemistry of amidoximes with that of conventional oximes.•Metal-mediated and metal-catalyzed reactions involving uncomplexed amidoximes.•Reactions of amidoxime ligands. Although the versatile chemistry of conventional oximes has been extensively reviewed over the years in both the organic chemistry literature and the coordination chemistry literature, amidoximes, RC(NH2)NOH, have so far received substantially less attention. Taking into account the increased publication activity on the subject, we systematically review the data on the routes for preparation of amidoxime complexes, the coordination patterns of ligands, and the classification of metal-involving reactions of amidoxime species. This survey includes a comparison of the coordination chemistry and metal-involving reactions of amidoximes with those of conventional ketoximes and aldoximes.